2017
DOI: 10.1371/journal.pone.0178194
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cannabis consumption: Psychometric properties of the Daily Sessions, Frequency, Age of Onset, and Quantity of Cannabis Use Inventory (DFAQ-CU)

Abstract: ObjectiveWe created the Daily Sessions, Frequency, Age of Onset, and Quantity of Cannabis Use Inventory (DFAQ-CU) because the current lack of psychometrically sound inventories for measuring these dimensions of cannabis use has impeded research on the effects of cannabis in humans.MethodA sample of 2,062 cannabis users completed the DFAQ-CU and was used to assess the DFAQ-CU’s factor structure and reliability. To assess validity, a subsample of 645 participants completed additional measures of cannabis depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(156 citation statements)
references
References 41 publications
2
153
1
Order By: Relevance
“…Despite using a validated measure of marijuana use quantity, the MUG focused on amount of grams participants’ used without querying the various forms of marijuana (e.g., leaf, concentrates, and edibles). Future researchers should query about marijuana use more comprehensively to obtain quantity estimates for the varying forms of marijuana (Cuttler and Spradlin, ). Relatedly, despite the psychometric support for the substance use motive measures (Chabrol et al., ; Grant et al., ), the coping subscales across these measures contained different item content, preventing us from examining whether these motives differ between alcohol and marijuana use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Despite using a validated measure of marijuana use quantity, the MUG focused on amount of grams participants’ used without querying the various forms of marijuana (e.g., leaf, concentrates, and edibles). Future researchers should query about marijuana use more comprehensively to obtain quantity estimates for the varying forms of marijuana (Cuttler and Spradlin, ). Relatedly, despite the psychometric support for the substance use motive measures (Chabrol et al., ; Grant et al., ), the coping subscales across these measures contained different item content, preventing us from examining whether these motives differ between alcohol and marijuana use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Studies have found that self-report of cannabis use is generally more accurate than other substances such as alcohol or methamphetamines (Arfer et al, 2018), and in the state where this study occurred, recreational cannabis is legal and well labeled in shops. Yet, at the time of this study, no well-validated and reliable instruments were available to measure cannabis consumption; therefore we modeled our items from those that were used by other cannabis researchers (Cuttler & Spradlin, 2017). Because our regression models examining frequency of cannabis alone were nonsignificant, it is possible that important differences exist depending on the type of cannabis products used.…”
Section: Discussionmentioning
confidence: 99%
“…Using skip logic, questions were further divided into three categories based on participant self-reported primary form of cannabis use, including flower or bud, concentrates (i.e., oils, wax, shatter, dabs), and edibles. In assessing the quantity of the flower or bud, a visual aid and terminology were adapted from the Daily Sessions, Frequency, Age of Onset, and Quantity of Cannabis Use Inventory (DFAQ-CU) (18).…”
Section: Methodsmentioning
confidence: 99%